Sophia and the Johannine Jesus - Scott, Martin (James Martin Clark) (Journal for the study of the New Testament. Supplement series ;, 1992)
This feminist approach to the Gospel of John explores the issue of the role of women in the Johannine Christian community. The author first examines in detail the relationship between the Jewish figure of Wisdom, known by the Greek name Sophia, and the Jesus of the Fourth Gospel. Secondly, he investigates what effect the use of a female figure as a basis for christological reflection have on the way in which women were portrayed in the Gospel. The deliberate choice of the feminine name Sophia caused problems for the writer of the Fourth Gospel in seeking to identify the exclusively female figu.